Educación y Desarrollo Humano, una Mirada desde la Generatividad - Martínez, Paola Macarena Juica (Cauriensia, 2023)
Undoubtedly, in the study of the educational practice it becomes particularly significant to analyze concepts such as generativity, understood as the expression of personal development in relation to self-care and care for others. This is because generative action is directly linked to the pedagogical exercise, as it promotes the intergenerational legacy through the formation and promotion of the integral development of the learner. In this context, this research seeks to contribute to the reflective analysis of the concepts related to education and human development, from its link with the generative potential. The research was conducted under a monographic approach, based on the bibliographic-documentary review and the critical, analytical and interpretative analysis of the subject sustained from the perspective of different authors, which yielded as main result that generativity, in its social dimension linked to education, not only benefits the development of those who receive the generative legacy, but also enhances and favors self-realization and self-care of those who exercise it, an argument on which the urgency of strengthening generative practices in all educational agents, especially among teachers, is determined.